Distributive fairness and local acceptance of wind turbines: The role of compensation schemes. (March 2020) - Leer Jørgensen, Marie; Anker, Helle Tegner; Lassen, Jesper
Abstract: To address increasing opposition to wind projects in Denmark three compensation schemes were introduced in the 2008 Renewable Energy Act. The aim was to address issues of distributive fairness and thereby to increase local acceptance. This paper analyses the role of two individual compensation schemes – the property value-loss scheme and the co-ownership scheme – on local citizens' perceptions of fair distribution of the benefits and burdens of wind energy projects. The qualitative case study of three Danish wind energy projects discloses that distributive unfairness was a prevalent concern among local citizens, and that this concern was inseparable from perceptions of procedural fairness and recognition. The key conclusion is that the two compensation schemes are not successfully offsetting perceptions of unfair distribution. The schemes are challenged by a multitude of intertwined concerns. The compensation schemes are not equipped to address the plethora of non-monetary values affected by the wind projects. Specifically the compensation schemes are criticised for not offering adequate local benefits or distribution thereof, equal access, fair procedures and transparency. In fact the schemes were by some considered unfair and created perceptions of lack of recognition and bribery which undermined their role in promoting distributive fairness and local acceptance. Highlights: Compensation schemes are not a panacea to promote local acceptance of wind energy. Two Danish schemes generally fail to redress concerns of unfair distribution among local citizens. The schemes do not address the plethora of non-monetary values of local citizens. They were perceived insufficient to address adverse impacts felt by local citizen. The results call for careful consideration of the design of compensation schemes.